Aspects of near-death experiences that bring about life change : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts at Massey University, Manawatū, New Zealand - Steadman, Kate (Massey University, 2015)
The literature on near-death experiences (NDEs) and its aftereffects is steadily growing. Common elements of a NDE have been widely documented, as well as a large body of common aftereffects. These aftereffects leave long lasting and dramatic impressions on the experiencers, yet no relationship between the content and features of a NDE and its aftereffects has been identified. The current study aims to investigate the relationship between NDE-related factors and their aftereffects in an Aotearoa New Zealand sample. Both quantitative and qualitative methods were used to obtain data in order to thoroughly investigate how NDEs manifest, how they are interpreted, and how they affect the people of Aotearoa New Zealand. Results showed that several situational factors and depth of participants NDEs were able to predict the degree of life changes they experienced as a result. Some evidence was provided to suggest that the type of NDE experienced also affected participants life changes. The current studies sample consisted of mostly New Zealand European/ Pākehā which limited ethnic interpretation of the findings. It is recommended that future studies include a culturally diverse sample of people from Aotearoa New Zealand to complement the culturally diverse nation. It is also recommended that further investigation in made into the direct relationship between NDE features and aftereffects in order to better understand what spurs such dramatic life changes.
Keywords: Near-death experiences; Psychological aspects; Life change events; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology